1985
DOI: 10.2737/rm-gtr-119
|View full text |Cite
|
Sign up to set email alerts
|

Aspen: Ecology and management in the western United States

Abstract: Information about the biology, ecology, and management of quaking aspen on the mountains and plateaus of the interior western United States, and to a lesser extent, Canada, is summarized and discussed. The biology of aspen as a tree species, community relationships in the aspen ecosystem, environments, and factors affecting aspen forests are reviewed. The resources available within and from the aspen forest type, and their past and potential uses are examined. Silvicultural methods and other approaches to mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(148 citation statements)
references
References 219 publications
2
139
0
Order By: Relevance
“…As an early seral species, aspen are poor competitors but have the ability to capitalize quickly on available resources (DeByle and Winokur 1985). These life history traits of aspen are clearly shown through the strong positive relationship between burn severity and post fire Fig.…”
Section: Management Wildfire and Aspen Regenerationmentioning
confidence: 95%
See 2 more Smart Citations
“…As an early seral species, aspen are poor competitors but have the ability to capitalize quickly on available resources (DeByle and Winokur 1985). These life history traits of aspen are clearly shown through the strong positive relationship between burn severity and post fire Fig.…”
Section: Management Wildfire and Aspen Regenerationmentioning
confidence: 95%
“…Post fire growing environment is of primary importance as our data clearly demonstrate that fire severity (measured via composite burn index; Key and Benson 2006), which directly reduces post fire biotic competition and indirectly increases soil moisture, soil temperature, and solar radiation (DeByle and Winokur 1985), is the most important predictor of post fire aspen sprout density and growth (Fig. 4, Cocking et al 2014).…”
Section: Management Wildfire and Aspen Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy browsing of aspen "suckers" in the first several growing seasons and during the initial growth period can eliminate a sucker stand and deplete the parent root system. In addition, ungulate use of adult aspens can scar the tree bole, which leads to an increase in canker infections (Patton and Jones 1977;DeByle and Winokur 1985).…”
Section: Birds -Desert-scrub and Shrubmentioning
confidence: 99%
“…Here we assess whether top-down and bottom-up interactions shape responses of a dominant ungulate herbivore along a gradient of abiotic conditions. We focus on elk because of their strong roles in affecting the demography and persistence of woody shrubs [12] that provide habitat for other species [13]. Previously, we demonstrated that the impact of elk herbivory on aspen (Populus tremuloides) in the Yellowstone Ecosystem is strongly affected by snow conditions [14].…”
Section: Introductionmentioning
confidence: 99%